2021
DOI: 10.1155/2021/5582140
|View full text |Cite
|
Sign up to set email alerts
|

How Government Regulations and Consumer Behavior Influence Manufacturers’ Product Green Degree Decision‐Making: An Agent‐Based Model

Abstract: In recent years, green product issues have received increasing attention. Both government regulations and consumer behaviors have a strong influence on the product green degree decisions of manufacturers’ products. In order to find how government regulations and individual’s green product purchase behavior affect manufacturers’ green degree decisions and the market evolution characteristics, this paper proposes a multiagent model that considers the interaction among government, consumers, and manufacturers. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 66 publications
2
6
0
Order By: Relevance
“…Green product price (D1) is a critical driving factor, which directly affects their willingness to purchase green products. This is consistent with previous research results [38,62]. Usually, due to the high quality and green attributes, the production cost of green products will be higher than that of similar traditional products.…”
supporting
confidence: 93%
“…Green product price (D1) is a critical driving factor, which directly affects their willingness to purchase green products. This is consistent with previous research results [38,62]. Usually, due to the high quality and green attributes, the production cost of green products will be higher than that of similar traditional products.…”
supporting
confidence: 93%
“…This finding contradicted previous research that used policy and regulation as an independent variable. Previous studies, such as Verma et al (2019) and Yuan et al (2021), concluded that government regulations significantly affected intention. However, those studies dealt with mandatory regulations that directly or legally impact the public or manufacturers.…”
Section: Construct Validity and Reliability Analysis Resultsmentioning
confidence: 93%
“…Previous studies, such as Verma et al . (2019) and Yuan et al . (2021), concluded that government regulations significantly affected intention.…”
Section: Resultsmentioning
confidence: 97%
“…PAS is the evaluation of an individual's understanding of the resources, guidelines, policies, and actions that could be supplied by the government or an authorized institution in order to carry out special actions [18]. The effect of government support on consumers may encourage them to make green decisions [52]. According to Persada et al [34], the government's involvement can have a significant impact on any commercial process, including those related to urban development.…”
Section: H6mentioning
confidence: 99%
“…An online questionnaire, which was adapted from related studies [18,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59], was used to build the items for measuring factors affecting sustainable behaviors related to buying sustainable products from name-brand shops. The measurement items were adapted and are referenced in Appendix A of Table A1.…”
Section: Questionnairementioning
confidence: 99%